2022
DOI: 10.3389/fonc.2022.868930
|View full text |Cite
|
Sign up to set email alerts
|

Use of Laparoscopic and Laparotomic J-Plasma Handpiece in Gynecological Malignancies: Results From A Pilot Study in A Tertiary Care Center

Abstract: IntroductionThe J-Plasma has recently been introduced into the surgical community with different intrinsic characteristics aimed to further reduce the thermal effect and enhance precision when compared to standard radiofrequency. This study aimed to investigate the role of this new technology in different conditions of gynecological carcinomatosis characterized by the indication for regional peritonectomy and/or ablation, either in laparotomy (LPT) or in laparoscopy (LPS), in the context of a modern personaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…According to their results, J-Plasma was applicable when the surgeons were facing disease on the bowel serosa without infiltration of the intestinal wall, on the diaphragmatic peritoneum and on the intestinal mesentery. Furthermore, in Gueli Alletti et al concluded that surgeons reached the learning curve after three procedures; a statement that was confirmed by our initial experience with J-Plasma device (18). The use of cold atmospheric helium plasma has been recently introduced into the surgical treatment for several different pathologies from several different specialties.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…According to their results, J-Plasma was applicable when the surgeons were facing disease on the bowel serosa without infiltration of the intestinal wall, on the diaphragmatic peritoneum and on the intestinal mesentery. Furthermore, in Gueli Alletti et al concluded that surgeons reached the learning curve after three procedures; a statement that was confirmed by our initial experience with J-Plasma device (18). The use of cold atmospheric helium plasma has been recently introduced into the surgical treatment for several different pathologies from several different specialties.…”
Section: Discussionmentioning
confidence: 60%
“…In the past, in order to achieve complete cytoreduction in such patients a bowel resection was inevitable. The use of plasma energy facilitates the removal of disease in the bowel serosa (rectal shaving) (18). With the use of J-Plasma such lesions on the bowel's mesentery could be removed without damaging the blood supply and without the need of bowel resection and anastomoses, procedures that add surgical time and possible intra-and postoperative complications such as leakage (Figure 5).…”
Section: Cancer Diagnosis and Prognosismentioning
confidence: 99%
“…The injury was smaller than that created with monopolar and bipolar ES devices. Furthermore, it was observed that the J-Plasma device (40% power, 4.0 l/min gas flow, 80 pulse setting) enabled the collection of peritoneal biopsies with cleaner edges compared to monopolar ES [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the last few decades, there has been a rapid succession of technological advances, marking a radical shift from the open to the minimally invasive surgical (MIS) approach [ 1 ]. The advantages of laparoscopy over laparotomy are now widely acknowledged [ 2 ].…”
mentioning
confidence: 99%